Real-time monitoring of single ZTP riboswitches reveals a complex and kinetically controlled decision landscape - Boyang Hua (Nature Portfolio, 2020)
Many RNAs become functional before their synthesis completes. Here the authors employ a single-molecule vectorial folding assay mimicking RNA transcription and show that the ZTP riboswitch is kinetically controlled and activated by slower unwinding and strategic pausing.